Pengaruh Inflasi dan Foreign Direct Investment (FDI) Terhadap Pengangguran Di Vietnam (2020-2024) - Rahmadani, Anggun Dwi; Haryono, Mazdhalia Yuli; Hasana, Fridayyah Citari; Dewanti, Nabila (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
This study is designed to examine the impact of inflation and foreign direct investment (FDI) on Vietnam’s economic conditions from 2020 to 2024. Using annual data and a linear regression approach, the results indicate that inflation has a significant effect on economic stability. FDI is also shown to contribute to economic activity, although its influence varies across sectors. The findings highlight the importance of controlling inflation and optimizing the utilization of FDI to support sustainable economic growth in Vietnam.